(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. El-Ghwas DE. 2021. Short Communication: Characterization and biological synthesis of zinc oxide nanoparticles by new strain of Bacillus foraminis. Biodiversitas 23: 548-553. The production of ZnO Nanoparticles (ZnONPs) has gained a lot of interest because of its wide antibacterial and eco-friendly activity. This work was performed for the biosynthesis of ZnONPs using isolated bacteria strains. A new bacterial strain isolated from farm soil in Jeddah, Saudi Arabia, was identified by molecular identification using 16S ribosomal RNA. The isolated sequence had the highest similarity (99 %) with Bacillus foraminis. On the other hand, the appearance of white precipitate at the end of incubation time confirms the production of ZnONPs. Also, UV, TEM, and FTIR were used to investigate the stability and structure of ZnONPs. The absorbance of ZnONPs was measured at 386 nm in a UV experiment. TEM result revealed that the particles were polydisperse and usually spherical, with maximum particles in the 5.40 - 6.79 nm range. In addition, FTIR confirms the reduction of zinc ions by bacteria. This is the first report on the biosynthesis of ZnONPs by B. foraminis.